Students' perception in using virtual reality device in English classroom - Siti Norzaimalina, Abd Majid; Rosnani, Ismail; Hafizoah, Kassim; Asiah, Kassim; Aisyah Hanum, Abu Bakar (Faculty of Educational Studies, Universiti Putra Malaysia Serdang, Selangor MALAYSIA, 2018)
Virtual reality technology has advanced immensely since 1990’s. The possibilities of utilizing VR in various fields are endless. In language learning, VR can provide realistic environment to practice language skills and also add fun to the learning. However, using virtual reality in language classroom is relatively new in Malaysian educational setting. This study aims to explore the students’ perception in using virtual reality device in English language classroom. Technology acceptance model by Davis (1989) is used as the framework. There were 137 students selected through convenient sampling. Data were analysed using descriptive statistics, correlation analysis and regression analysis. The findings showed that intention to use virtual reality device was strongly influenced by perceived usefulness. Overall, students’ perception on using VR in English classroom was positive